The effects of the decline of a keystone plant species on a dune community plant-pollinator network - Sandacz, Dan; Vitt, Pati; Knight, Tiffany M.; CaraDonna, Paul; Havens, Kayri (Frontiers in Conservation Science, 2023)
Ecological communities are maintained through species interactions, and the resilience of species interactions is critical to the persistence of natural communities. Keystone species play outsized roles in maintaining species interaction networks, and within plant-pollinator communities are high priorities for conservation. The loss of a keystone plant from a plant-pollinator network is expected to cause changes to network structure and composition of pollinator species, with the potential to cause secondary losses of plants and pollinators. To understand how the unmanipulated decline of a keystone plant affects the structure and composition of its network, we studied the plant-pollinator interactions of a Lake Michigan dune plant community where the population of the keystone plant, Cirsium pitcheri, is in rapid decline. The network prior to C. pitcheri decline (2016) was compared to the network as C. pitcheri continued to decline (2021 and 2022) in response to habitat loss. We find evidence that the loss of C. pitcheri altered network structure such that the community may be more sensitive to perturbations. Furthermore, changes in the composition of pollinators were explained by species turnover to a greater extent than by interaction rewiring, including the loss of bumblebees. Short-term negative consequences based on the changes to network structure and composition might lead to long-term effects on the persistence of the dune community. Our study exemplifies that the decline of a keystone plant can have negative implications for conservation of a plant-pollinator community. Using an interaction network framework to assess plant-pollinator communities has potential to develop strategies for best conservation and restoration practices in habitats vulnerable to habitat loss and disturbance.